No match for money: Even in intimate relationships and collectivistic cultures, reminders of money weaken sociomoral responses - Savani, Krishna (2017)
The present research tested two competing hypotheses: (1) as money cues activate an exchange orientation to social relations, money cues harm prosocial responses in communal and collectivistic settings; (2) as money can be used to help close others, money cues increase helping in communal or collectivistic settings. In a culture, characterized by strong helping norms, money cues reduced the quality of help given (Experiment 1), and lowered perceived moral obligation to help (Experiment 2). In communal relationships, money reminders decreased willingness to help romantic partners (Experiment 3). This effect was attenuated among people high on communal strength, although money cues made them upset with help requests (Experiment 4). Thus, the harmful effects of money on prosocial responses appear robust.